Optimization of the GSH-Mediated Formation of Mesoporous Silica-Coated Gold Nanoclusters for NIR Light-Triggered Photothermal Applications - Fernandes, Natanael (2021)
Cancer light-triggered hyperthermia mediated by nanomaterials aims to eliminate cancer cells by inducing localized temperature increases to values superior to 42 C, upon irradiation with a laser. Among the different nanomaterials with photothermal capacity, the gold-based nanoparticles have been widely studied due to their structural plasticity and advantageous physicochemical properties. Herein, a novel and straightforward methodology was developed to produce gold nanoclusters coated with mesoporous silica (AuMSS), using glutathione (GSH) to mediate the formation of the gold clusters. The obtained results revealed that GSH is capable of triggering and control the aggregation of gold nanospheres, which enhanced the absorption of radiation in the NIR region of the spectra. Moreover, the produced AuMSS nanoclusters mediated a maximum temperature increase of 20 C and were able to encapsulate a drug model (acridine orange). In addition, these AuMSS nanoclusters were also biocompatible with both healthy (fibroblasts) and carcinogenic (cervical cancer) cells, at a maximum tested concentration of 200 g/mL. Nevertheless, the AuMSS nanoclusters’ NIR light-triggered heat generation successfully reduced the viability of cervical cancer cells by about 80%. This confirms the potential of the AuMSS nanoclusters to be applied in cancer therapy, namely as theragnostic agents.